THE IMPACT OF CODE-SWITCHING ON STUDENTS' LEARNING PROCESS AND PSYCHOLOGICAL REGULATION IN BILINGUAL CLASSROOM: A PERSPECTIVE FROM EDUCATIONAL PSYCHOLOGY - Mawardi, Mohammad Maqbul; Ruhiyah, Fida; Mubarok, Ghozi; Majid, Ach. Nurholis (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
This study explores the impacts of code-switching practices in the teaching and learning process in bilingual schools. The background of this study is based on the fact that the use of code-switching practices not only impacts linguistic and academic aspects but also has significant implications for students' psychological conditions, such as building emotional closeness between teachers and students through humour, praise, and empathetic expressions. Therefore, the purpose of this study is to identify the impacts of code-switching on students' learning process and psychological regulation in bilingual language learning. The research method used in this study is a library research with a descriptive qualitative approach, referring to various scientific sources such as journal articles, books, and relevant research reports. The results of this study show several impacts of code-switching in the teaching and learning process. First, code-switching helps the students comprehend the lessons and achieve great success. Teachers switch their language when they give feedback, check students' understanding, make conclusions, clarify information, and explain specific information. Second, code-switching is used to control the students' enthusiasm and behaviour. Solidarity and intimate relationships between teachers and students are the elements that cannot be neglected in the education sector. Applying code-switching as a communication strategy to create humour is an effective way to support learning situations.